AWARENESS AND PRACTICES APPLIED BY HEALTH CARE WORKERS TO ACHIEVE PATIENT SAFETY DURING PHLEBOTOMY AND ULTRASOUND BIOPSY - Balooch, Salahuddin; Noureen, Fakhra; Khan, Abid Saeed; Rehman, Ibad ur; Bakhtawar, Aleena; Raza, Waseem (Pakistan Armed Forces Medical Journal, 2020)
Objective: To assess awareness and practices applied by health care workers to achieve patient safety during phlebotomy and ultrasound biopsy. Study Design: Cross-sectional study Place and duration of study: The present study was conducted from Jan 2019 to Jan 2020 at Combined Military Hospital (CMH), Kharian, Pakistan. Patients and Methods: The health care providers were interrogated about their knowledge and practices regarding patient safety with respect to phlebotomy and ultrasound biopsy. The responses of participants were evaluated through correlation analysis by SPSS v.17. Results: The results show that awareness and practice implementation for patient safety in phlebotomy and ultrasound biopsy enhance in accordance to age, education and experience. The findings of present study suggest that physicians and nurses tend to have better awareness and practices of patient safety as compared to other health care workers. However, all the health care workers included in present study showed adequate level of awareness and practice implementation. Conclusion: The managers and co-workers need to support the health care workers’ groups that tend to show lower levels of awareness and practice implantation in patient safety. This will not only enhance their competence but also help in better and secure provision of health care.